Drone shipping versus truck delivery in a cross-docking system with multiple fleets and products - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos-Arteaga, Francisco J.; Zandi, Mohammad-Hossein (Expert systems with applications, 2017)
•We propose a new bi-objective multi-product combined cross-docking truck-scheduling model.•The model allows for direct drone shipping from supplier to customers and multiple fleets.•An efficient multi-objective epsilon-constraint method is adapted to solve the model.•The efficient Pareto frontiers are estimated by generating non-dominated solutions.•We analyze the effects that changes in direct shipping costs have on the Pareto frontiers. We propose a new bi-objective multi-product combined cross-docking truck-scheduling model with direct drone shipping and multiple fleets.The proposed model considers two conflicting objective functions (scheduling cost and time) within a multi-objective mixed integer mathematical programming problem. Several constraint sets are also considered for both allocation and scheduling phenomena. An efficient multi-objective epsilon-constraint method is adapted to solve the proposed model. Several numerical examples and metrics are provided to demonstrate the applicability of the proposed model and exhibit the efficacy of the solution procedures and algorithms. The efficient frontiers of the numerical examples are estimated by generating non-dominated solutions. The effects that modifications in the costs associated with the direct shipping of products have on the corresponding Pareto frontiers are analyzed. Finally, sensitivity analysis is used to assess the robustness of the results of the model in the presence of uncertainty. [Display omitted]